Life cycle assessment of particleboard - Mohd Azman, Muhammad Aiman Hakim (2020)
The Life Cycle Assessment Method was used in this study to assess the environmental impacts of the particleboard. The objective is to analyse the chemical content of the particleboard and to identify the impact of particleboard towards the environment. Environmental issues have become the main concern in the world, and the use of formaldehyde as a binder of particleboard that can lead to human carcinogens. This life-cycle analysis consists of four stages, which are based on ISO 14044 and ISO 14040. The phases are goal and scope definition phase, the inventory analysis phase, the impact assessment phase and the interpretation phase. The categories of impact that had been assessed were global warming, abiotic resource depletion, human toxicity, ecotoxicity, marine aquatic ecotoxicity, ozone layer depletion, photochemical oxidation and terrestrial ecotoxicity. In the product analysis step, the particleboard was examined using the FTIR computer. The FTIR system can produce results consisting of a material that is embedded in the particleboard. The results were further analysed using the openLCA. With the aid of the FTIR study, this software provides the final results for particleboard life-cycle evaluation. As a consequence, the development of particleboards applied 100% to all environmental parameters, except for abiotic resource depletion and ozone depletion.